High-resolution small-angle x-ray diffraction study of long-range order in hard-sphere colloidal crystals. - Petukhov, A; Aarts, D; Dolbnya, I; De Hoog, E; Kassapidou, K; Vroege, G; Bras, W; Lekkerkerker, H (2002)
The long-range order parameters in single crystals of hard colloidal spheres grown in sediments of colloid-polymer mixtures are determined using synchrotron small-angle x-ray diffraction with a resolution of 10(-6) of the wave vector. The interplanar positional order derived from the width of lattice reflections extends over at least 500 lattice planes. The lattice planes are orientationally correlated within approximately 0.1 degrees throughout the crystals, whereas the stacking of hexagonal planes remains random.